2004
DOI: 10.1111/j.1365-2036.2004.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and pharmaceutical cost of sequential treatment for Helicobacter pylori in patients with non‐ulcer dyspepsia

Abstract: SUMMARYBackground: A novel 10-day sequential treatment regimen recently achieved a significantly higher eradication rate than standard 7-day therapy in both peptic ulcer disease and non-ulcer dyspepsia. Its higher performance has recently been confirmed using a halved clarithromycin dose in peptic ulcer disease. Aims: To evaluate whether an acceptable eradication rate could also be obtained by halving the clarithromycin dose in dyspeptic patients and to assess the role of possible factors affecting the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The sum is doubled when the therapy duration is prolonged to 10-14 d, as suggested by some reports [28] . If sequential therapy is used, the cost of treatment is about 40 € but the therapeutic gain is unsatisfactory.…”
Section: Cost/benefit Implications In Italysupporting
confidence: 53%
“…The sum is doubled when the therapy duration is prolonged to 10-14 d, as suggested by some reports [28] . If sequential therapy is used, the cost of treatment is about 40 € but the therapeutic gain is unsatisfactory.…”
Section: Cost/benefit Implications In Italysupporting
confidence: 53%
“…The availability of new rescue therapies would make it possible to combine the classical drugs, amoxicillin, clarithromycin and metronidazole in first line therapy. Among the new promising alternatives to triple therapy, a 10-day sequential therapy combining a five day course of amoxicillin and a proton pump inhibitor with five days of clarithromycin, metronidazole and a proton pump inhibitor was recently described (43)(44)(45)(46). This treatment seems to be effective even in patients with clarithromycin resistance and is the first therapy that has proved superior to triple therapy in a large randomized trial (47).…”
Section: Discussionmentioning
confidence: 96%
“…30 Several studies have reported higher eradication rates of H. pylori than standard triple therapy. [31][32][33] However, some reports in areas such as France and Spain showed 85% of unsatisfactory rates of eradication, while Thailand (96%) and Taiwan (92%) showed satisfactory rates. 34,35 A study showed that sequential therapy was significantly more effective in children infected with clarithromycin resistant strains (81 vs. 13%).…”
Section: Discussionmentioning
confidence: 99%